Cervical fusion for degenerative disease: A comprehensive cost analysis of hospital complications in the United States from 2002 to 2014 - Hansen Deng; John K Yue; Angel Ordaz; Ernesto J Rivera; Catherine G Suen; David C Sing (Journal of Craniovertebral Junction and Spine, 2018)
Purpose: Recent data suggest great variability in costs for surgical hospitalization for spinal surgery. However, the magnitude of expenditures attributable to complications is unknown. The purpose of this study is to describe cost of care associated with surgical and medical complications after cervical spine surgery. Materials and Methods: A retrospective cohort study utilizing the National Inpatient Sample years 2002–2014 was conducted. A weighted sample of 901,508 adults undergoing elective cervical fusion for degenerative indications was extracted using diagnostic and procedure codes. Twelve categories of major complications were identified, and patient/hospital variables were evaluated as predictors of the overall reimbursed cost using multivariate regression. Mean differences (B) and 95% confidence intervals were reported. Results: The mean age was 52.2 ± 11.4 years, with 5.2% of patients experiencing a complication. Mean overall increase in inflation-adjusted cost associated with complication was $16,435 ± 10,358, varying significantly by type of complication, surgical approach, and number of levels fused. The most common complications and their attributed costs were dysphagia (1.6%, B = $2624 [2476–2771], P < 0.001), pulmonary complications (1.0%, B = $9334 [9110–9558], P < 0.001), and device-related complications (0.9%, B = $3125 [2927–3324], P < 0.001). The costliest complications were infection (0.1%, B = $25359 [24723–25994], P < 0.001), thromboembolism (0.1%, B = $17480 [16808–18153], P < 0.001), and neurological complications (0.2%, B = $10098 [9629–10567], P < 0.001). Conclusions: Although complications are rare after elective cervical fusion, they are associated with dramatically increase costs of care as high as $25,359 in the setting of postoperative infection. Improved understanding of the economic magnitude of complications may help guide efforts in reducing health care spending and improving perioperative care.